PKM Kerajinan Tangan Miniatur Kapal Pinisi Di Kecamatan Rappocini Kota Makassar - Mustari; Sitti Hajerah Hasyim; Ratnah S; Nur Arisah; Nahriana (CV. Aksara Global Akademia, 2023)
This article aims to make a handicraft product using bamboo as the main material, namely a miniature Phinisi ship which is made to be more familiar with Makassar culture and can have high economic selling value, it is hoped that it can be marketed and as a learning medium for the product, as well as helping the community consumptive by fulfilling the desire for unique items that are in demand by many groups. In this activity, the methods used include lectures, questions and answers or discussions, and training offers creativity by exploring innovative forms to make it more attractive and can be adapted to consumer needs with this product which is expected not only to be a medium for learning history but also to generate profits.